1997
DOI: 10.1161/01.atv.17.10.2209
|View full text |Cite
|
Sign up to set email alerts
|

Altered Compliance and Residual Strain Precede Angiographically Detectable Early Atherosclerosis in Low-Density Lipoprotein Receptor Deficiency

Abstract: Early atherosclerosis in LDL-receptor deficient rabbits, undetectable by angiography yet observed by intravascular ultrasound imaging and histology, is associated with marked changes in ex vivo residual strain. Alterations in vascular biomechanical properties, associated with changes in cholesterol content, may have physiologic consequences and may be useful in detecting and quantitating early atherosclerosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 64 publications
1
15
0
1
Order By: Relevance
“…In contrast, carotid IMT quantitatively measures the arterial morphology consisting of intimal lesions and medial hypertrophy 25) . In animal studies it has been shown that altered arterial compliance precedes angiographically detectable atherosclerosis in LDL-receptor deficient rabbits 26) . Furthermore, the Atherosclerosis Risk in Communities (ARIC) study demonstrated that there was no association between arterial wall thickness and increased arterial stiffness, except for the thickest 10% of the artery walls 27) ; therefore, arterial stiffness and carotid atherosclerosis may differ in the pathologic background and be dissociated in time.…”
Section: Fig 1 Correlation Between Circulating Chemerin Levels and mentioning
confidence: 99%
“…In contrast, carotid IMT quantitatively measures the arterial morphology consisting of intimal lesions and medial hypertrophy 25) . In animal studies it has been shown that altered arterial compliance precedes angiographically detectable atherosclerosis in LDL-receptor deficient rabbits 26) . Furthermore, the Atherosclerosis Risk in Communities (ARIC) study demonstrated that there was no association between arterial wall thickness and increased arterial stiffness, except for the thickest 10% of the artery walls 27) ; therefore, arterial stiffness and carotid atherosclerosis may differ in the pathologic background and be dissociated in time.…”
Section: Fig 1 Correlation Between Circulating Chemerin Levels and mentioning
confidence: 99%
“…Similar observa- All measurements are meanϮSD. tions have been reported by Hong et al 18 : Intravascular ultrasound had identified circumferential wall thickening in 6-month-old heterozygous HHL rabbits, whereas angiography failed to detect any changes. MR-based visualization of the vascular wall requires adequate spatial resolution coupled with sufficient signal strength and homogeneity.…”
Section: Discussionmentioning
confidence: 67%
“…In animal models, aortic stiffening precedes the development of atherosclerosis [40,41], and when atherosclerosis occurs, aortic compliance correlates inversely with the atherosclerotic burden [42]. In the Framingham Heart Study, an increased pulse pressure, which is a reflection of increased arterial stiffness, was associated with cardiovascular events over 20 years of follow-up [43].…”
Section: Discussionmentioning
confidence: 99%